A Case of Melioidosis Presenting as Migrating Pulmonary Infiltration: The First Case in Korea - Lee, Sei Won (The Korean Academy of Medical Sciences, 2005)
Melioidosis is an infection of the Gram-negative bacterium Burkholderia pseudomallei. While it is known as an important cause of sepsis or chronic abscess-forming disease in Southeast Asia and northern Australia, no case has yet been reported in Korea. A 50-yr-old man visited our hospital for intermittent fever associated with dry cough and sputum. Roentgenographic examination showed migrating pulmonary infiltration. Symptoms and chest radiograph and computed tomography (CT) image findings did not improve despite use of fluoroquinolone antibiotics. Gram-negative bacteria were isolated on bronchoscopic washing culture and were identified as B. pseudomallei on DNA sequencing of 16S ribosomal RNA with 100% homology. Treatment for melioidosis was commenced with high dose ceftazidime, and the patient's fever, cough, and sputum were improved and the lesion on chest radiograph and CT almost disappeared.